Kompatibilitas Metode Pembuktian dan Penafsiran Hakim Konstitusi dalam Putusan Pemilukada - Helmi Kasim; Syukri Asy’ari; Meyrinda R. Hilipito; Rio Tri Juli Putranto (Jurnal Konstitusi, 2012)
Decision-making in the Settlement of Local Election Dispute at the Constitutional Court is based on the conviction of the justices after examining evidence submitted by the parties. Meanwhile, the law has limited the authority of the Court which is simply to rule on the result of vote count in the local election. Therefore, through interpretation, the Court has created new norms in its decision concerning local election.In some of its decisions, the Court broadened its authority in the settlement of local election dispute which is to include the process of the election. The dictum of the decision does not merely follow what is stated in the law. There is compatibility in the justices’ conviction based on interpretation done by the justices regarding   the authority of the Court in deciding Local Election Dispute and in the choice of dictum of the decision which is different from what has been stated by the law.